Status of Dental Caries and Oral Health Behaviour among 6 to 9 Years Children Attending at a Dental College Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Oral hygiene is the method that is used to `prevent pathological condition that affect mouth like gum disease, cavities, mouth sores and ulcers.Objective: The purpose of this study was to observe oral health behavior among the children of 6 to 9 years’ old such as regular tooth brushing, uses of oral hygiene aids and dental attendance to maintain their good oral health for a life time.Methodology: This cross-sectional study conducted in Dhaka Dental College and Hospital, Bangladesh study was carried out from October 2019 to September 2020. A total of 175 participants’ children aged 6 to 9 years attending at the OPD with dental Caries in Dhaka Dental College Hospital were the study population. The study population were included children aged 6 to 9 years in Dhaka dental college and hospital who were available and wished to participate. The questionnaire was used in this study pre-tested before the data collection, data was collected using semi-structured questionnaire by face-to-face interview.Results: A total of 175 children were examined during the study. Among them 65.13% were suffering from caries teeth. Among the majority of children (40.57%) dental caries was from government primary school as compare from private primary school (15.43%). The dmft score of 1 or higher increases with the increasing age of the children. 7 to 8 years’ children (20.57%) had high dmft score. High DMFT score indicates significant relation between age of children and dmft scores (P=.000,